Perampasan Aset Korupsi Tanpa Pemidanaan Dalam Perspektif Hak Asasi Manusia - Teuku Isra Muntahar; Madiasa Ablisar; Chairul Bariah (Iuris Studia: Jurnal Kajian Hukum, 2021)
Confiscation of assets without conviction or NCB using the principle of presumption of guilt is an effective alternative in returning criminal assets, but faces challenges on the basis of human rights violations. This normative research discusses the problem of NCB's conflict with human rights violations. It was concluded that, the existing regulations have not regulated NCB but are in accordance with the constitution (Article 28H paragraph 4 and Article 28G paragraph 1 of the 1945 Indonesian Constitution), Article 29 paragraph (2) DUHAM / UDHR, Article 70 and Article 29 paragraph (1) UUHAM , European Human Rights Commission Decree 1986, and ICJ Decree 1959, where the state has the authority to control illegal assets or tainted with corruption. The UUPTPK still adheres to criminal forfeiture, depending on criminal wrongdoing, only applies if the perpetrator dies, does not apply if the criminal error is not proven, cannot seize the assets of no-owner and third party assets Its application is not against human rights if during the NCB process the third party is still given the opportunity to argue and is not done arbitrarily. The principle of presumption of guilt is aimed at assets, while the principle of presumption of innocence is directed at the perpetrator. Nor does it contradict the principle of ne bis in idem because civil suit and criminal prosecution are two different things. It is hoped that the Asset Confiscation Bill is corrected and promulgated, then regulates the NCB in the UUPTPK, improves MLA regulations for civil matters. The application must be carried out with extreme caution because it is vulnerable to human rights violations